2008
DOI: 10.1007/s11095-008-9679-z
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Rotating Disk Intrinsic Dissolution Rate Measurement: Effects of Buffer Capacity in Comparisons to Traditional Wood’s Apparatus

Abstract: The results demonstrate that using 100-fold less drug does not sacrifice the quality of the measurement, and lends support to an earlier study Yu et al. (Int. J. Pharm. 270:221-227, 2004) that the disk IDR measurement may possibly serve as a surrogate for the BCS solubility classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 38 publications
0
104
0
Order By: Relevance
“…Intrinsic dissolution tests have been reported for numerous single component pharmaceutical materials (Avdeef and Tsinman, 2008;Mauger et al, 2003;O'Connor and Corrigan, 2001;Yu et al, 2004) whereas little literature is found for cocrystals (Childs et al, 2004;Jung et al, 2010;Lee et al, 2011;Rahman et al, 2011). The intrinsic dissolution rate is based on measurements of powder compacts of known surface area under conditions of controlled hydrodynamics (Healy et al, 2002) and is described as particle-size independent (Hendriksen and Williams, 1991;Wood et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic dissolution tests have been reported for numerous single component pharmaceutical materials (Avdeef and Tsinman, 2008;Mauger et al, 2003;O'Connor and Corrigan, 2001;Yu et al, 2004) whereas little literature is found for cocrystals (Childs et al, 2004;Jung et al, 2010;Lee et al, 2011;Rahman et al, 2011). The intrinsic dissolution rate is based on measurements of powder compacts of known surface area under conditions of controlled hydrodynamics (Healy et al, 2002) and is described as particle-size independent (Hendriksen and Williams, 1991;Wood et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…The type of water was not specified in 19 of 51 studies (37%) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Watermentioning
confidence: 99%
“…This happens in rotating-disk dissolution studies, where hydrochloride salts of weak-base drugs dissolve quickly but then re-precipitate in the pH 6.8 phosphate buffer media as free bases on the surface of the dissolving rotating drug salt pellet (e.g., as shown visually for papaverine in Fig. 4 in Avdeef and Tsinman, 2008). This would not happen with perphenazine, since it had been introduced as a free base (cf., Fig.…”
Section: Solid Form Isolated From Suspensionsmentioning
confidence: 99%